SUBMICRON AIRBORNE DUST PARTICLE MONITORING SYSTEM - ROMAN, Cecilia; ROMAN, Marius; DORDAI, Lucian; KOVACS, Eniko; HOAGHIA, Maria-Alexandra; PUSKAS, Ferenc (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The harmful effects of airborne dust have been long known, with numerous studies proving the danger it poses to human health. The paper presents a submicron size airborne dust particle monitoring system, built in collaboration by a laboratory equipment manufacturer and a national research and development institute. The system is designed for the automotive industry, the printed circuit board production lines, and the environmental monitoring. It can measure and record data continuously and the loss of the supply voltage does not lead to the loss of the monitoring history. The key element is the particle sensor itself, consisting of a laser diode assembly - CCD area, a suction pump with continuous operation, with constant electronically controlled flow and an electro-optical detector. The system is designed with the following specifications: the applicable particle size: 0.3 μm; 0.5 μm; 1.0 μm; sampling time: 1…599 sec; programmable (25 sec. by default); average count setting: 2; 4; 8; 16; 32; 64; ambient temperature range: operating at 40ºC; power: 220V / 50 Hz; power consumption: max. 25 VA; ABS housing, IP rating 54; dimensions (L x W x D): 260 x220 x 156 mm; weight: approximately 2.5 kg.